2001
DOI: 10.1207/s15327957pspr0502_7
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Conferred Conceptions of Agency: A Key to Social Perception of Persons, Groups, and Other Actors

Abstract: Many tendencies in social perceivers 'judgments about individuals and groups can be integrated in terms of the premise that perceivers rely on implicit theories of agency acquired from cultural traditions. Whereas American culture primarily conceptualizes agency as a property of individual persons, other cultures conceptualize agency primarily in terms ofcollectives such as groups or nonhuman actors such as deities or fate. Cultural conceptions ofagency exist in publicforms (discourses, texts, and institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 56 publications
4
146
1
2
Order By: Relevance
“…One way to understand these findings is that in each culture emotions are constructed based on information that is most consequential to agency. Agency in European Americans is based within the individual, whereas agency in Asian Americans may be grounded in the family or group [43] (see also Markus, this special issue).…”
Section: Cultural Construction Of Emotions: Individual-level Processesmentioning
confidence: 99%
“…One way to understand these findings is that in each culture emotions are constructed based on information that is most consequential to agency. Agency in European Americans is based within the individual, whereas agency in Asian Americans may be grounded in the family or group [43] (see also Markus, this special issue).…”
Section: Cultural Construction Of Emotions: Individual-level Processesmentioning
confidence: 99%
“…Through the tendency to make fundamental attribution errors, the information that most closely supports the attribution will be attended to and serve to fulfill expectations. Furthermore, it has been shown that the manner in which individuals make attributions vary across cultures (see Morris, Menon, & Ames, 2001;Norenzayan & Nisbett, 2000;Choi, Dalal, Kim-Prieto, & Park, 2003).…”
Section: Perceived Riskmentioning
confidence: 99%
“…If agency is conceptualized in terms of collectives such as groups, families or organizations (e.g., Morris, Menon, & Ames, 2001), taking away a group freedom feels threatening. Also when agency is primarily conceptualized as coming from being in relationships, taking away an interpersonal freedom is experienced as threatening.…”
Section: Theoretical Implicationsmentioning
confidence: 99%